The evolutionary origins and diversity of the neuromuscular system of paired appendages in batoids. Issue 1914 (6th November 2019) - Turner, Natalie; Mikalauskaite, Deimante; Barone, Krista; Flaherty, Kathleen; Senevirathne, Gayani; Adachi, Noritaka; Shubin, Neil H.; Nakamura, Tetsuya
Abstract : Appendage patterning and evolution have been active areas of inquiry for the past two centuries. While most work has centred on the skeleton, particularly that of amniotes, the evolutionary origins and molecular underpinnings of the neuromuscular diversity of fish appendages have remained enigmatic. The fundamental pattern of segmentation in amniotes, for example, is that all muscle precursors and spinal nerves enter either the paired appendages or body wall at the same spinal level. The condition in finned vertebrates is not understood. To address this gap in knowledge, we investigated the development of muscles and nerves in unpaired and paired fins of skates and compared them to those of chain catsharks. During skate and shark embryogenesis, cell populations of muscle precursors and associated spinal nerves at the same axial level contribute to both appendages and body wall, perhaps representing an ancestral condition of gnathostome appendicular neuromuscular systems. Remarkably in skates, this neuromuscular bifurcation as well as colinear Hox expression extend posteriorly to pattern a broad paired fin domain. In addition, we identified migratory muscle precursors (MMPs), which are known to develop into paired appendage muscles with Pax3 and Lbx1 gene expression, in the dorsal fins of skates. Our results suggest that muscles of paired fins have evolved via redeployment of the genetic programme of MMPs that were already involved in dorsal fin development. Appendicular neuromuscular systems most likely have emerged as side branches of body wall neuromusculature and have been modified to adapt to distinct aquatic and terrestrial habitats.